Centrality dependence of charged particle production at large transverse momentum in Pb-Pb collisions at √sNN=2.76 TeV$h - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; et al. (Physics letters, 2013)
The inclusive transverse momentum (pT) distributions of primary charged particles are measured in the pseudo-rapidity range |η|<0.8 as a function of event centrality in Pb-Pb collisions at sNN=2.76 TeV with ALICE at the LHC. The data are presented in the pT range 0.15<pT<50 GeV/c for nine centrality intervals from 70-80% to 0-5%. The results in Pb-Pb are presented in terms of the nuclear modification factor RAA using a pp reference spectrum measured at the same collision energy. We observe that the suppression of high-pT particles strongly depends on event centrality. The yield is most suppressed in central collisions (0-5%) with RAA≈0.13 at pT=6-7 GeV/c. Above pT=7 GeV/c, there is a significant rise in the nuclear modification factor, which reaches RAA≈0.4 for pT>30 GeV/c. In peripheral collisions (70-80%), only moderate suppression (RAA=0.6-0.7) and a weak pT dependence is observed. The measured nuclear modification factors are compared to other measurements and model calculations.